Stratigraphy and sedimentology of Azokh Cave, South Caucasus. - Murray, J.; Lynch, E.; Dominguez-Alonso, P.; Barham, Milo (Springer, 2016)
The Pleistocene to Holocene stratigraphy of sediments from three entrance passages to Azokh Cave, Lesser Caucasus, is presented. The larger Azokh 1 passage preserves approximately 11–12 m of in situ cave-fill, divisible into nine stratigraphic units based on their sedimentary characteristics. The base of the succession (Units IX to VI) is predominantly non-fossiliferous, but becomes both fossiliferous and calcareous upwards and displays evidence of fluvial and cave spall deposition. The upper part of the succession (Units V to I) is a (largely) continuous sequence of generally fossiliferous fine-grained sediments dating from the Middle Pleistocene to the present. The Pleistocene-Holocene transition is not represented in the succession due to a marked erosional disconformity between Units II and I (at the top of the sequence). The entrance passage to Azokh 2 contains a fill of at least 1.65 m depth that is divisible into two distinct units, whilst the interior of Azokh 5 has revealed at least 4.5 m of cave-filling sediment, which is divisible into five stratigraphic units (A–E). Unit A, at the top of the Azokh 5 sequence, has produced charcoal which provided an age of 2.3 ka and sits with marked discontinuity on the irregular upper surface of Unit B below. The ages of the units beneath this level are unknown at present.